Change in Vitamin D Levels and Risk of Severe Vitamin D Deficiency over 48 Weeks among HIV-1-Infected, Treatment-Naive Adults Receiving Rilpivirine or Efavirenz in a Phase III Trial (Echo). Issue 2 (February 2014) - Wohl, David A; Orkin, Chloe; Doroana, Manuela; Pilotto, José H; Sungkanuparph, Somnuek; Yeni, Patrick; Vanveggel, Simon; Deckx, Henri; Boven, Katia
Background: This analysis assessed changes in serum 25-hydroxyvitamin D (25[OH]D; the precursor form of active vitamin D) in antiretroviral-naive adults receiving rilpivirine or efavirenz over 48 weeks in a randomized, double-blind, Phase III trial (ECHO). Methods: ECHO included 690 patients randomized 1:1 to receive rilpivirine 25 mg once daily ( n =346) or efavirenz 600 mg once daily ( n =344), plus tenofovir disoproxil fumarate/emtricitabine. 25(OH)D was measured in stored serum samples collected at baseline, and weeks 24 and 48. Proportions of patients with optimal/sufficient (≥30 ng/ml), insufficient (21–29 ng/ml), deficient (10–20 ng/ml) and severely deficient (<10 ng/ml) 25(OH) D levels were determined. Data are presented for patients with paired baseline and week 48 25(OH)D data (rilpivirine, n =292; efavirenz, n =290). Results: After 48 weeks, mean 25(OH)D levels remained largely unchanged from baseline with rilpivirine (-0.2 ng/ml; P =0.57 versus no change), but were significantly reduced with efavirenz (-2.5 ng/ml; P <0.0001 versus no change). When adjusting for season of randomization and the combined variable of race (Black/African American, White/Caucasian, Asian, other race) and ethnicity (Hispanic or Latino and not Hispanic or not Latino), the conclusion about the treatment difference between the rilpivirine and efavirenz treatment groups remained valid. At baseline the proportion of patients with severe 25(OH)D deficiency was similar in both groups (5%) but was significantly lower with rilpivirine than efavirenz at week 48 (5% versus 9%, respectively; P =0.032). Furthermore, of the patients with 25(OH)D insufficiency/deficiency at baseline, the proportion who developed severe 25(OH)D deficiency at week 48 was significantly lower with rilpivirine than efavirenz (2% versus 8%, respectively; P =0.0079). Conclusions: Rilpivirine had little effect on 25(OH)D, whereas efavirenz resulted in a significant reduction in 25(OH)D levels and an increase in the risk of severe 25(OH)D deficiency.